THE RIGHTS OF INDONESIAN WORKERS: BETWEEN NORMS AND REALITY IN THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Kelana, Dewa Sukma; Fautanu, Idzam; Saepullah, Usep (SINERGI : Jurnal Riset Ilmiah, 2026)
This research examines the gap between legal norms and the reality of protecting the rights of Indonesian Migrant Workers (TKI) and their impact on families in the perspective of Islamic family law. Although Indonesia has comprehensive regulations such as Law No. 18/2017 on the Protection of Indonesian Migrant Workers, its implementation is still far from expectations. Structural problems cause violations of migrant workers' rights that have an impact on family disintegration, neglect of maintenance obligations, and marital conflict. This research uses a juridical-normative method with statutory, conceptual, and shar'i approaches. Data were collected through a literature study of primary and secondary legal materials, then analyzed descriptively-qualitatively and comparatively. The results show that there is a significant gap between legal guarantees and actual protection of migrant workers, which results in the neglect of family rights as regulated in Islamic law. The perspective of Islamic family law offers solutions through the principles of justice (al-'is), benefit (maslahah), and protection (hifzh). The research recommends the integration of Islamic law values in migrant worker protection policies, strengthening the role of the family as a protection unit, and harmonizing positive law with sharia principles to realize family-based holistic protection.